Tandem-pore K+ channels mediate inhibition of orexin neurons by glucose. - Burdakov, D; Jensen, LT; Alexopoulos, H; Williams, R; Fearon, I; O'Kelly, I; Gerasimenko, O; Fugger, L; Verkhratsky, A (2006)
Glucose-inhibited neurons orchestrate behavior and metabolism according to body energy levels, but how glucose inhibits these cells is unknown. We studied glucose inhibition of orexin/hypocretin neurons, which promote wakefulness (their loss causes narcolepsy) and also regulate metabolism and reward. Here we demonstrate that their inhibition by glucose is mediated by ion channels not previously implicated in central or peripheral glucose sensing: tandem-pore K(+) (K(2P)) channels. Importantly, we show that this electrical mechanism is sufficiently sensitive to encode variations in glucose levels reflecting those occurring physiologically between normal meals. Moreover, we provide evidence that glucose acts at an extracellular site on orexin neurons, and this information is transmitted to the channels by an intracellular intermediary that is not ATP, Ca(2+), or glucose itself. These results reveal an unexpected energy-sensing pathway in neurons that regulate states of consciousness and energy balance.